A cohort study of multiple families with FBN1 p.R650C variant, ectopia lentis, and low but not absent risk for aortopathy. Issue 11 (21st September 2017) - Vatti, Lohith; Fitzgerald‐Butt, Sara M.; McBride, Kim L.
Abstract : Marfan syndrome is a multisystem disease with cardiovascular, ophthalmologic, and skeletal features. Diagnosis is made clinically with emphasis on presence of aortic root dilation and ectopia lentis (EL). Most individuals meeting these criteria have a pathogenic variant in FBN1, usually unique or observed rarely. Individuals with EL alone may also have FBN1 pathogenic variants, and the risk for aortic disease is not well known. We identified a unique cohort of 31 individuals (mean age 29, range 2–78) from nine families ascertained by a proband with EL alone, who had the same FBN1 p.R650C variant. Comparison was made to individuals with Marfan syndrome ( n  = 103 from 97 families) at our institution. Those with the p.R650C variant had few skeletal features of Marfan syndrome. Age of onset of EL was later compared to others with cysteine variant changes. Aortic root dilation occurred in 4/16 (25%) of the p.R650C group versus 71/83 (86%) in the comparator group ( p  < 0.001) and dissection or replacement in 1/31 (3%) versus 20/103 (19%; p  < 0.04). Aortic root Z scores were much lower in the p.R650C (0.34 ± 1.70) versus the comparator (2.99 ± 2.54; p  < 0.0002). Kaplan–Meier failure curves for aortic root dilation demonstrated later age of onset and differed significantly for incidence rate ratio (comparator vs. p.R650C = 5.35, CI 1.84–21.17; p  = 0.0001). Individuals with p.R650C predominantly have EL, but do have risk for aortic dilation at ages later than typical for Marfan syndrome in general and for cysteine changes specifically. Surveillance for aortic dilation is required but may occur less frequently.